Lead-free multilayer ceramic capacitors with ultra-wide temperature dielectric stability based on multifaceted modification. Issue 3 (March 2022) - Liu, Xudong; Hou, Yudong; Song, Beibei; Cheng, Huarong; Fu, Yutong; Zheng, Mupeng; Zhu, Mankang
Abstract: The rapid development of high technology—such as space exploration and electric vehicles—urgently requires ultra-wide temperature multilayer ceramic capacitors (UWT MLCCs) to achieve reliable operation of electronic circuits in harsh environments. However, simultaneously achieving high dielectric permittivity, low dielectric loss, and ultrahigh thermal stability has been a major challenge for practical dielectric ceramics. The co-firing matching of the internal electrode and the dielectric ceramic is also an important factor that affects the reliability of UWT MLCCs. Herein, through multifaceted modification—i.e., composition design related to the modulation of the local polar nanoregions (PNRs) and optimizing device sintering in the context of the compatibility of the heterogeneous interface—these concerns have been well-addressed. A new lead-free dielectric system (1- x ) (0.56Na0.5 Bi0.5 TiO3 -0.14K0.5 Bi0.5 TiO3 -0.3NaNbO3 )- x CaZrO3 (NKBTNN- x CZ) dominated by P4bm PNRs was designed and corresponding UWT MLCCs with reliable Pt internal electrode interface bonding were fabricated by optimizing the sintering temperature. A record-high dielectric permittivity ( ε r = 839 ± 15 %) and low dielectric loss (tanδ ≤0.02) was achieved over an ultra-wide temperature range from -70 °C to 337 °C for NKBTNN-0.063CZ UWT MLCCs. This work suggests that multifaceted modification should be generalized for construction of high-performance UWT MLCCs.